2020
DOI: 10.3389/fpsyg.2019.03014
|View full text |Cite
|
Sign up to set email alerts
|

Different Patterns of Sleep-Dependent Procedural Memory Consolidation in Vipassana Meditation Practitioners and Non-meditating Controls

Abstract: Aim: Rapid eye movement (REM) sleep, non-rapid eye movement (NREM) sleep, and sleep spindles are all implicated in the consolidation of procedural memories. Relative contributions of sleep stages and sleep spindles were previously shown to depend on individual differences in task processing. However, no studies to our knowledge have focused on individual differences in experience with Vipassana meditation as related to sleep. Vipassana meditation is a form of mental training that enhances proprioceptive and so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 123 publications
2
7
0
Order By: Relevance
“…Despite post-training meditation failing to establish a distinct benefit for sleep-dependent motor consolidation as compared to control, as expected, the offline improvements in both groups exhibited from training to post-sleep test supports a wealth of research in favor of sleep-dependent gains in performance (Diekelmann & Born, 2010). As mentioned, research by Solomonova et al (2020) investigated whether meditation practice changes the neurobiological qualities of sleep-dependent memory consolidation by comparing the performance of experienced Vipassana meditators with meditation naïve individuals on a procedural balance task. Though both groups experienced improved performance as anticipated via sleep, the way in which these improvements arose were distinct.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Despite post-training meditation failing to establish a distinct benefit for sleep-dependent motor consolidation as compared to control, as expected, the offline improvements in both groups exhibited from training to post-sleep test supports a wealth of research in favor of sleep-dependent gains in performance (Diekelmann & Born, 2010). As mentioned, research by Solomonova et al (2020) investigated whether meditation practice changes the neurobiological qualities of sleep-dependent memory consolidation by comparing the performance of experienced Vipassana meditators with meditation naïve individuals on a procedural balance task. Though both groups experienced improved performance as anticipated via sleep, the way in which these improvements arose were distinct.…”
Section: Discussionsupporting
confidence: 71%
“…Though both groups experienced improved performance as anticipated via sleep, the way in which these improvements arose were distinct. The experienced meditators improvements were correlated with occipital spindle density in non-rapid eye movement (NREM) sleep, however the controls task improvements were correlated with increased time in rapid eye movement (REM) sleep (Solomonova et al, 2020). The authors note that previous training on attending to bodily states and stimuli might generate a different neurobiological way of learning which might help explain previous findings showing an enhanced level of attention is associated with improved motor performance (Hazeltine et al, 1997).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The fact that meditation has been found to improve cognitive performance in the absence of sleep, aligns well with the theory that the meditative state itself may facilitate some of the restorative functions of sleep, which may ultimately lead to improved cognitive performance (Guerriero et al, 2019;Nagendra et al, 2012;Solomonova et al, 2020). These results further corroborate Guerriero et al's (2019) assertion that meditation might exert its overall influence on cognition through its ability to improve (and perhaps even mimic) restorative sleep.…”
Section: Could Meditation Improve Cognition Through Sleep?supporting
confidence: 68%
“…The authors interpreted these findings as suggesting that meditation potentially induces a reorganization of sleep microarchitecture, which may lead to different patterns of sleep-dependent memory consolidation in experienced practitioners. They also suggested that meditation practice itself might compensate for the memory functions of sleep (Solomonova et al, 2020). Taking these various studies together, it becomes more plausible that meditation's effects on cognition may be mediated through sleep, as opposed to having any direct effects as is normally assumed.…”
Section: Could Meditation Improve Cognition Through Sleep?mentioning
confidence: 99%